2018
DOI: 10.24820/ark.5550190.p010.668
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of sucrose 1’-position modification with 3-(trifluoromethyl)diazirinyl benzylbromide derivatives for photoaffinity labeling

Abstract: Sucrose is well known as naturally occurring sweeteners. Photoreactive sucrose derivative containing 3-(trifluoromethyl)diazirinyl moiety is designed for photoaffinity labeling. As 1'-hydroxyl group of sucrose is well known to be less reactive than other primary alcohols, the optimization of reaction conditions for diazirinyl benzyl bromide derivative at sucrose 1'-postion was examined to elucidate the functional analysis of sweet receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…This phenomena also occurred when sucrose was used. 12,16,17 According to these approaches, the bromination product of 1-kestose was determined to be 1'',2,3,3',3'',4,4',4''-octa-O-acetyl-6,6',6''-tribromo-6,6',6''-trideoxy-1-kestose (4).…”
Section: Resultsmentioning
confidence: 99%
“…This phenomena also occurred when sucrose was used. 12,16,17 According to these approaches, the bromination product of 1-kestose was determined to be 1'',2,3,3',3'',4,4',4''-octa-O-acetyl-6,6',6''-tribromo-6,6',6''-trideoxy-1-kestose (4).…”
Section: Resultsmentioning
confidence: 99%
“…at 60 °C for 24 h afforded a moderate yield (∼60%) for benzylation. 30 However, the conditions with large excess were not suitable for rare benzyl halide derivatives. A detailed analysis of the reaction mixture revealed that the benzyl alcohol derivatives were generated under the reaction conditions.…”
Section: Photoaffinity Probes For Sweetener Derivativesmentioning
confidence: 99%